Trzy intrygujące aspekty świadectwa w Psalmach - Węgrzyniak, Wojciech (Verbum Vitae, 2015)
The aim of this article is to analyze three difficult aspects of testimony in the Book of Psalms: (1) the term עֵדוּת‘ēdût in the titles of certain Psalms (Ps 60:1; 80:1); (2) understanding who or what is referred to as a witness in Ps 89:38; and (3) the proper translation of עֵדוּת ‘ēdût, and its meaning, in its multiple uses in Ps 119. First, as background, the author synthetically depicts what the psalms say generally regarding the notion of testimony. Proceeding to the focal issues, he first analyzes עֵדוּת ‘ēdût in the titles of the two psalms and concludes that the term should be interpreted as an independent title and translated as “testimony”. The next section presents the current understandings of who or what is a witness in Ps 89:38 (rainbow, sun, moon, throne, God), and proposes a new messianic interpretation. In the final part, after the presentation of various translations, the author suggests interpreting עֵדוּת ‘ēdût in Psalm 119 as a technical term, properly translated in Psalm 119 always as “testimony”.